Calculation of Expansibility Factor of Gas at Its Flow Through an Orifice Plate with Flange Pressure Tappings - Yevhen Pistun; Leonid Lesovoy (Energy Engineering and Control Systems)
The values of expansibility factor of gas were defined more accurately based on the values obtained by Seidl in CEESI using the equation of mass flowrate and on the basis of experimental data (differential pressure across the orifice plate, mass flowrate, absolute static pressure and temperature of air) for orifice plates with flange pressure tappings and diameter ratios of 0.242, 0.363, 0.484, 0.5445, 0.6655, 0.728 and pipe internal diameter of 52.48 mm (2.066 in.). When obtaining the values of expansibility factor of gas, the Stolz equation was used by Seidl to calculate the discharge coefficient for Reynolds numbers equal to infinity. New values of expansibility factor of gas are defined more accurately by us with taking into account the Reader-Harris/Gallagher equation for calculating the discharge coefficient for the actual Reynolds numbers of gas in the pipe. Based on these new more accurate data a new equation for calculating the expansibility factor of gas for orifice plate with flange pressure tappings is developed. The comparison and analysis of the expansibility factor calculated according to the equation given in ISO 5167:2-2003 and according to the new developed equation is presented in the paper. The equation in ISO 5167:2-2003 for computing the gas expansibility factor is developed for all three types of pressure tappings arrangement. In this case the scattering of discharge coefficient values being applied for deriving the expansibility factor equation is large for the same set of input data. It is shown that the shortcomings mentioned above are eliminated in the new equation and the standard deviation of the expansibility factor calculated according to the new equation from the new accurate experimental values is smaller. New formula for calculating the relative expanded uncertainty of expansibility factor for orifice plate with flange pressure tappings is also presented in the paper.